Aging Relevant Metabolite Itaconate Inhibits Inflammatory Bone Loss - Wang, Yuting; Li, Song; Zhao, Liming; Cheng, Peng; Liu, Jian; Guo, Fengjing; Xiao, Jun; Zhu, Wentao; Chen, Anmin (Frontiers in Endocrinology, 2022)
Progressive bone loss during aging makes osteoporosis one of the most common and life impacting conditions in geriatric populations. The bone homeostasis is maintained through persistent remodeling mediated by bone-forming osteoblast and bone-resorbing osteoclast. Inflammaging, a condition characterized by increased pro-inflammatory markers in the blood and other tissues during aging, has been reported to be associated with skeletal stem/progenitor cell dysfunction, which will result in impaired bone formation. However, the role of age-related inflammation and metabolites in regulation of osteoclast remains largely unknown. In the present study, we observed dichotomous phenotypes of anti-inflammatory metabolite itaconate in responding to inflammaging. Itaconate is upregulated in macrophages during aging but has less reactivity in responding to RANKL stimulation in aged macrophages. We confirmed the inhibitory effect of itaconate in regulating osteoclast differentiation and activation, and further verified the rescue role of itaconate in lipopolysaccharides induced inflammatory bone loss animal model. Our findings revealed that itaconate is a crucial regulatory metabolite during inflammaging that inhibits osteoclast to maintain bone homeostasis.